How to Write a Staff Manual : A Guide for Managers - Brock, Susan L.; Cabbell, Sally R. (London Kogan Page Ltd., 1998)
Whatever the size of your organization, a staff manual is a key document for all your employees. As a first point of reference it helps avoid misunderstandings when questions arise on procedures, policies and conditions of employment. And with everyone receiving the same information, you know that it can only improve administration and your organization's sense of identity.
Include Index.
A Guide for Managers.
Keywords: Management -- Communication in organizations